After the first lockdown due to the COVID-19 pandemic: Perceptions, experiences, and effects on well-being in Italian people - Covelli, Venusia; Camisasca, Elena; Manzoni, Gian Mauro; Crescenzo, Pietro; Marelli, Alessandra; Visco, Marina Angela; Cafagna, Dario; Marsicovetere, Vincenzo; Pesce, Mario; Cantoia, Manuela (Frontiers in Psychology, 2023)
Despite the COVID-19 pandemic and the subsequent measures of containment have stimulated multiple studies aimed at assessing their impacts on people's psychophysical well-being, few studies investigated people's experiences on general population by adopting a mixed-method approach. An online survey was conducted in the period following the first lockdown in Italy. Psychological well-being, perceived stress and COVID-19-related fears were assessed by standardized questionnaires (Psychological General Well-Being Index-Short version, Perceived Stress Scale 10, and Multidimensional Assessment of COVID-19-Related Fears). Experiences and perceptions related to the lockdown period were also evaluated by means of an open-ended question. A total of 855 subjects completed the survey. Results show a lower level of well-being compared to normative levels, and a high level of both perceived stress and fear of contracting the virus. The thematic analysis of responses to the open-ended question was carried out through the T-Lab software. Two factors and five clusters were revealed, which explain the thematic variance among the narratives: the first factor refers to the type of experience (positive vs. negative), while the second refers to the type of context (home vs. work). Results confirm the effectiveness of the mixed-method approach for an in-depth and exhaustive investigation of people’s psychological condition during and after the first lockdown.